2007 7th IEEE Conference on Nanotechnology (IEEE NANO) 2007
DOI: 10.1109/nano.2007.4601325
|View full text |Cite
|
Sign up to set email alerts
|

A fresh look at majority multiplexing when devices get into the picture

Abstract: In this paper we present the first detailed analysis of von Neumann multiplexing (vN-MUX) using majority (MAJ) gates of small fan-ins ǻ (MAJ-ǻ) with respect to the probability of failure of the elementary (nano-)devices. Only gates with small fan-ins have been considered, as gates with large fan-ins do not seem practical (at least in the short term) in future technologies. The extensions from an exact counting algorithm (for gate defects and faults only) to device-level failures will allow us to estimate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Although a wealth of papers reporting performance analyses of vN-MUX have been published [26]- [34], the analysis in [25] was the first one to consider the devices' probabilities of failure (PFDEV), the gates' topologies, and the input vectors to accurately analyze the performance of vN-MUX schemes. The simulation results reported in [25] have shown that MAJ-3 vN-MUX at RF = 6 outperforms NAND-2 vN-MUX at RF = 9 by a reliability improvement index (RII, see eq.…”
Section: Introductionmentioning
confidence: 99%
“…Although a wealth of papers reporting performance analyses of vN-MUX have been published [26]- [34], the analysis in [25] was the first one to consider the devices' probabilities of failure (PFDEV), the gates' topologies, and the input vectors to accurately analyze the performance of vN-MUX schemes. The simulation results reported in [25] have shown that MAJ-3 vN-MUX at RF = 6 outperforms NAND-2 vN-MUX at RF = 9 by a reliability improvement index (RII, see eq.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reliability techniques include functional redundancy. Common techniques include R-fold modular redundancy (RMR), including triple modular redundancy (TMR) as the most common implementation [3], [4]- [6], cascaded TMR (CTMR) [3], [7], different multiplexing schemes [4], [8]- [16], and reconfiguration [17]- [20]. Each of these techniques has an optimal space of application, depending on defect density, type of defects, and size of a chip.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques like RMR and CTMR require very coarse granularity level (10 6 -10 7 devices in a redundant unit) and low device failure probability (10 −8 -10 −7 ) [3], [7]. On the other hand, techniques like NAND/MAJ multiplexing could be efficient at finer granularity levels and higher device failure probability, requiring moderate redundancy factors (10-100) [11]- [16]. Reconfiguration offers good performance in terms of tolerable defect density and granularity level, but cannot correct transient errors and needs long testing/configuration time [3], [11], [20].…”
Section: Introductionmentioning
confidence: 99%
“…The RMR technique requires a very coarse granularity level (10 6 to 10 7 devices in a redundant unit [6]) and low device failure probability (10 −8 to 10 −7 ) [2]. On the other hand, techniques like NAND/MAJ multiplexing could be efficient at finer granularity levels and higher device failure probability, requiring moderate redundancy factors (10-100) [7], [9]. Reconfiguration offers the best performance in terms of tolerable defect density and granularity level, but cannot correct transient errors and needs long testing/configuration time [2], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, taking (8) into consideration, it becomes clear that P block f ails, (2) from (11) is negligible compared to P block f ails from (9). Since the joint probabilities for reliable blocks are negligible, the chip fails if any of the outputs of any reliable block fails; hence, the upper bound probability that the whole chip fails is…”
mentioning
confidence: 99%